(untitled) (Journal of Applied Oral Science, 2012)
OBJECTIVES: The aim of this study was to analyze the immunolabeling of two cell cycle protein regulators, p53 and p21WAF1, in non-dysplastic leukoplakias with different epithelial alterations: acanthosis, hyperkeratosis and acanthosis combined with hyperkeratosis, and compare them with dysplastic leukoplakias. MATERIAL AND METHODS: This was a prospective cohort study involving 36 patients with oral homogeneous leukoplakias. excisional biopsies were performed and the patients remain under clinical follow-up. The leukoplakias were divided into four groups: 6 acanthosis, 9 hyperkeratosis, 10 acanthosis combined with hyperkeratosis, and 11 epithelial dysplasias. Paraffin-embebeded sections were immunostained for p53 and p21WAF1. Five hundred cells from the basal layer and 500 from the parabasal layer were counted to determine the percentage of positive cells. A qualitative analysis was also carried out to determine the presence or absence of immunohistochemical staining in the intermediate and superficial layers. Groups were compared with ANOVA (p